A Healthy Environment for a Healthy Mind: Mental Health Risks Attached to Poor Housing among Congolese refugees living in Yeoville, Johannesburg - Dostin Mulopo Lakika (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
This article explores spatial inequality as a conceptual framework to understand the link between poor housing, environmental degradation, and mental health. The dire housing conditions are one of the many struggles that refugees face in South Africa. This paper emerged from fieldwork carried out between 2020 and 2022 among Congolese refugees in Yeoville, a suburb of Johannesburg. They were included in a research project investigating the existing association between displacement, gendered violence, and mental ill-health among internally displaced persons, refugees, and asylum seekers. The article highlights that while mental health challenges can result from various factors, poor housing adds profound psychological distress to Congolese refugees in South Africa. Drawing on 83 interviews with male and female Congolese refugees, this article highlights how precarious housing disrupts traditional, social, and cultural structures. It also weakens parents’ control over their children, invades privacy, exposes women and girls to sexual violence, and contributes to the fragility of family bonds. The findings of this paper emphasize the importance of spatial inequality in examining the precarious housing conditions experienced by refugees in South Africa. These conditions, which occur in seemingly abandoned environments, have a detrimental impact on the mental health of Congolese refugees.